2021
DOI: 10.1186/s12943-021-01463-y
|View full text |Cite
|
Sign up to set email alerts
|

Cancer associated-fibroblast-derived exosomes in cancer progression

Abstract: To identify novel cancer therapies, the tumor microenvironment (TME) has received a lot of attention in recent years in particular with the advent of clinical successes achieved by targeting immune checkpoint inhibitors (ICIs). The TME consists of multiple cell types that are embedded in the extracellular matrix (ECM), including immune cells, endothelial cells and cancer associated fibroblasts (CAFs), which communicate with cancer cells and each other during tumor progression. CAFs are a dominant and heterogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
113
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 180 publications
(116 citation statements)
references
References 200 publications
3
113
0
Order By: Relevance
“…One of the key components that mediate intracellular communication in the tumor microenvironment is exosomes ( 31 ). For instance, it is reported that exosomes derived from melanoma cells increase the differentiation of human umbilical vein endothelial cells into cancer-associated fibroblasts, and the latter ones promote cancer progression ( 32 ). Another study discloses that exosomes derived from adenocarcinoma gastric cancer cells promote the migration and invasion of adipose-derived MSCs through transmitting circular RNA 0004303 ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…One of the key components that mediate intracellular communication in the tumor microenvironment is exosomes ( 31 ). For instance, it is reported that exosomes derived from melanoma cells increase the differentiation of human umbilical vein endothelial cells into cancer-associated fibroblasts, and the latter ones promote cancer progression ( 32 ). Another study discloses that exosomes derived from adenocarcinoma gastric cancer cells promote the migration and invasion of adipose-derived MSCs through transmitting circular RNA 0004303 ( 33 ).…”
Section: Discussionmentioning
confidence: 99%
“…The stromal cells, particularly cancer-associated fibroblasts (CAFs), can promote tumor cell survival mainly by recruiting immune cells into the TME, and promote invasion by constructing a hypoxic environment. Tumor-driven hypoxia, increased inflammation, or MMPs overexpression in the TME induces alterations in the ECM, following the tumor biological behavior of evading apoptosis, elevating invasion and metastasis ( 17 , 18 ). In addition, ECM components can regulate the cancer-immunity cycle.…”
Section: Tumor Microenvironment and Antiangiogenic Therapymentioning
confidence: 99%
“…It is possible that the rate of CAF-exosome secretion may also change based on ECM density/stiffness and could serve as an independent prognostic factor. The literature showing the growing number of exosomal molecules which could serve as potential biomarkers supports this hypothesis [49] .…”
Section: Discussionmentioning
confidence: 88%